Induction of double-strand breaks by S1 nuclease, mung bean nuclease and nuclease P1 in DNA containing abasic sites and nicks. - Chaudhry, M A (1995)
Defined DNA substrates containing discrete abasic sites or paired abasic sites set 1, 3, 5 and 7 bases apart on opposite strands were constructed to examine the reactivity of S1, mung bean and P1 nucleases towards abasic sites. None of the enzymes acted on the substrate containing discrete abasic sites. Under conditions where little or no non-specific DNA degradation was observed, all three nucleases were able to generate double-strand breaks when the bistranded abasic sites were 1 and 3 base pairs apart. However, when the abasic sites were further apart, the enzymes again failed to cleave the DNA. These results indicate that single abasic sites do not cause sufficient denaturation of the DNA to allow incision by these single-strand specific endonucleases. The reactivity of these enzymes was also investigated on DNA substrates that were nicked by DNasel or more site-specifically by endonuclease III incision at the discrete abasic sites. The three nucleases readily induced a strand break opposite such nicks.